Poetic Devices and Rubrics on Luisa Gluck “An Adventure” - Sihite, Jubilezer; Simandalahi, Sabam Taruna (Syntax Literate, 2021)
Poetry has a mystery contained in the choice of words a magical touch that can make the reader lulled. Through structures, certain issues can be addressed in a deeper analysis. The researcher focuses on the poetic device of Luisa Gluck's poetry "An Adventure". Poetic approach is used to find out the characteristics of poetry and to find out the values. There are two research problems in this study: what are the poetic tools used in the poetry and how are the results of using rubric. The first is answered by using a poetic device approach. Poetry is analysed based on the type of poetic devices: allegory, alliteration, figure of speech, imagery, assonance etc. The second is answered by calculating scores using rubric. A good poem can be judged by considering several important points to get a rating of whether a poem is bad, fair, good or very good